Soziale Bürgerrechte im Museum: Die Repräsentation sozialer Demokratie in neun kulturhistorischen Museen - Jäger, Wolfgang (transcript, 2020)
The history of democracy in the museum lacks the representation of social democracy. A critical analysis of large permanent exhibitions.